2011
DOI: 10.3928/01484834-20111017-03
|View full text |Cite
|
Sign up to set email alerts
|

Using Quality and Safety Education for Nurses to Guide Clinical Teaching on a New Dedicated Education Unit

Abstract: Gaps exist in health professional education versus the demands of current practice. Leveraging front-line nurses to teach students exemplary practice in a Dedicated Education Unit (DEU) may narrow this gap. The DEU is an innovative model for experiential learning, capitalizing on the expertise of staff nurses as clinical teachers. This study evaluated the effectiveness of a new academic-practice DEU in facilitating quality and safety competency achievement among students. Six clinical teachers received educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 6 publications
2
29
0
Order By: Relevance
“…In evaluation of QSEN competency skills, the majority of the students reported that they felt "developing and accomplished" on survey items. This finding confirms from a study conducted by McKown, McKeon, and Webb (2011) where authors evaluated the effectiveness of a new academic-practice unit in facilitating QSEN competency achievements among 12 students, and they found that the majority of students achieved QSEN competencies through clinical mentoring in interdisciplinary collaboration, using electronic information for best practice and patient teaching, patient/family decision making, quality improvement, and resolution of safety issues. Pauly-O'Neill, Prion, and Nguyen (2013) also reported that three of the six QSEN competency skills were observed more often than the others during clinical experiences.…”
Section: Discussionsupporting
confidence: 76%
“…In evaluation of QSEN competency skills, the majority of the students reported that they felt "developing and accomplished" on survey items. This finding confirms from a study conducted by McKown, McKeon, and Webb (2011) where authors evaluated the effectiveness of a new academic-practice unit in facilitating QSEN competency achievements among 12 students, and they found that the majority of students achieved QSEN competencies through clinical mentoring in interdisciplinary collaboration, using electronic information for best practice and patient teaching, patient/family decision making, quality improvement, and resolution of safety issues. Pauly-O'Neill, Prion, and Nguyen (2013) also reported that three of the six QSEN competency skills were observed more often than the others during clinical experiences.…”
Section: Discussionsupporting
confidence: 76%
“…Ideally, students are able to achieve quality practice and safety competencies in facilitative learning environments established through collegial academic and practice partnerships. [1] Setting the conditions for optimal student nurse clinical practice, however, remains challenging worldwide. Issues reported in the literature include: lack of close supervision of students by clinical staff due to nursing shortages and inadequate collaboration between clinical staff and academia; [2] inadequate or scarce clinical placement sites, often as a consequence of increased numbers of students; [3,4] reduction in traditional clinical placement opportunities related to health system changes; [4] competition with other health disciplines for the same practice settings; [2][3][4] shortages of academically qualified faculty members; [2,5,6] and, academic expectations that influence faculty workloads and make it difficult to hire and retain faculty with current clinical expertise or for faculty members to maintain their clinical expertise.…”
Section: Introductionmentioning
confidence: 99%
“…A few examples of this movement include the dedicated education units at the Methodist University Hospital in Tennessee and the educational resource unit at ProMedica Health System in Ohio. 17,18 Both programs aimed at decreasing the preparation-practice gap that existed in nursing education. They both demonstrated effective academic-practice partnership models that addressed the need to educate both the students and the nursing workforce on quality and safety principles through the QSEN framework.…”
Section: What Does It Mean To the Nurse Leader?mentioning
confidence: 99%